Sports College Education Under the Background of the Development of Sports Undergraduate Education - Yuting Zhou, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The establishment of sports-oriented undergraduate education and the transformation of vocational education systems have introduced significant pressures and challenges for sports colleges. Yet, considering the broader context of actual economic and social developments and international experiences in sports education, the central role of sports colleges within the modern vocational education system remains unaltered. The unique social and economic value provided by sports college education is indispensable. In response to emerging challenges, sports college education must engage in self-reflection to emphasize its contemporary relevance. This involves adhering to the principles of high-quality development, clarifying the objectives of talent training specific to sports, enhancing the educational quality, fortifying distinctive educational features, and streamlining the professional athlete training system. Such strategic focuses are essential to sustain and advance the role of sports colleges in nurturing proficient sports professionals in the evolving educational landscape.